An Overview Pericardium 6 Acupressure Therapy as Hypovolemic Risk Prevention for Gastritis Patients In Emergency Department - Sari, Ni Luh Putu Lucky Hennesia Novita; Sanjana, I Wayan Edi; Sukadana, I Gede (Babali Emergency and Disaster Research, 2024)
Background: Gastritis is an inflammation of the stomach wall, especially the gastric mucosa. A common problem in gastritis patients is nausea or nausea which causes a feeling of discomfort in the back of the throat or stomach which can result in vomiting). Management of nausea in gastritis patients can be through independent actions of nurses or with pharmacological and non-pharmacological actions. One of the nurse's independent actions that can be done is acupressure pericardium (pc) 6. Purpose: To determine the effectiveness of pericardium 6 acupressure therapy on reducing nausea in gastritis patients at Klungkung Regency Hospital as a prevention of hypovolemic risk. Methods: This final scientific work uses a case study design. The subjects in this final scientific work used two patients in nursing problems with one medical diagnosis of gastritis with the nursing problem of nausea. Results: The results showed that two patients who experienced complaints of nausea after being given acupressure intervention pericardium 6 in gastritis patients said nausea complaints were reduced. Conclusion: From interventions and research related to the effectiveness of giving acupressure therapy pericardium 6, it is proven effective in reducing nausea experienced by patients with gastritis.